PENGEMBANGAN BUKU CERITA BERGAMBAR PADA KETERAMPILAN MEMBACA SISWA TEMA 2 MENYAYANGI TUMBUHAN DAN HEWAN SUBTEMA 4 MENYAYANGI HEWAN PEMBELAJARAN 1 - Irma Kurniasih; Wawan Syahiril Anwar; Stella Talitha (STKIP Subang, 2023)
A picture story book is a book that contains stories accompanied by pictures or illustrations to support the contents of the story. Reading is a useful activity that can provide various information. Indonesian reading skills are still relatively low. This study aims to get a picture story book product with theme 2 loving plants and animals sub-theme 4 loving learning animals 1 in class III SDN Cibunar 01 with a total of 20 students as respondents. This development uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of the validation test of linguists, materials, and media experts show that picture story books are valid and very feasible to use to obtain an average percentage of 80%. In the limited trial phase as many as 20 students gave a positive response to the picture story books used. Based on the results of the study, it can be concluded that the picture story book developed in this study proved to be valid, interesting and very useful for use in students' reading skills.